From farm to table - Dieffenbach, Michael; Streed, Sarah; Deepbrook Productions; Write Stuff Works; Learning Seed Company (Illinois : Learning Seed, 2007)
Takes a comprehensive look at modern agriculture and discusses where, why, and how it evolved. Examines the whole process of food production and distribution, from the Neolithic Revolution and the dawn of farming to the rise of industrial agriculture and the Green Revolution
Title from title screen
DVD Format
Optional English subtitles
Keywords: Food industry and trade; Food